Three female impersonators - Sahl, Ted (photographer):::Creator::::::::::::
Three female impersonators pose with a male at Bucks Saloon. Two dartboards can be seen in the background. From left to right: Alexis, Vena Las Vegas, Dennis Andrews, Lucy Manhattan (Ms. Gay South Bay).